EFFECT OF FUNCTIONAL FEED ADDITIVES ON EGG PRODUCTION, HATCHABILITY AND HEMATOLOGICAL TRAITS OF JPANESE QUAILS DURING SUMMER CONDITION - & et al., Mustafa (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2017)
The present study was conducted to investigate the effect of using functional feed additives on egg production, hatchability and hematological traits of Japanese quails under hot weather condition. A total of 288 a day old of Japanese quail were allocated to six treatments with three replicates containing T0: control, T1: Optifeed® 500g/ton feed, T2: Oleobiotec®100g/ton feed, T3: Force®6 100g/ton, T4: VêO® premium 250 g/ton feed and T5: mixing of (Optifeed® 250g + Oleobiotec® 50g+ Force®6 (50 g)+VêO® premium 125 g)/ton.The results were summarized that the functional feed additives were significantly higher in body weight, body weight gain in T1 and T5, high economic profit in T1, T4 and T5 and FCR improved in T1, T3, T4 and T5 at age 35 day old, egg production percentage and economic profit and food conversion ratio (FCR) more improvement in the all treatments of feed additives, feed intake in T1 and T3 at ages (36-70) day old. Also higher Haugh unit, egg weight, eggshell thickness, eggshell strength, egg yolk lipids, RBCs, Hb, PCV, the serum concentrations of (HDL, antioxidant activity and GPx), fertility, hatchability of fertile egg, hatchability of total egg, hatched chicks weight and immunological ELISA titer against Newcastle (ND), Gamboro (IBD) and Infectious bronchitis diseases, also improved in H/L ratio in feed additives treatments. Whereas; significantly lower of cholesterol and malondialdehyde in the egg yolk, the concentrations of total cholesterol, LDL, VLDL, malondialdehyde in the serum, the percentages of dead embryos at ages: early (1-7) d, mid (8-14) d, late (15-17) d, total (1-17) d and disabled chicks in feed additives treatments compared with the control. However; there were no significant differences between control and experimental treatments in mortality at ages 35 and 70 days old and the relative weight of eggshell. From the results all feed additives that used in this experiment had positively effect on body performance, economic profit at 35 days old, also positively affected on egg production percentage, egg quality and improved blood parameters, hatchability and quails immunity during summer months.